Clinical Characteristics and Outcomes of the First Episode of Urinary Tract Infection in Neonates and Infants Younger than 2 Months of Age - Jackie Ying-Wai Cheng (Childhood Kidney Diseases, 2017)
Purpose The American Academy of Pediatrics provides guidelines for managing febrile urinary tract infection (UTI) in infants and children 2-24 months old, but little guidance is offered regarding UTIs in those younger than 8 weeks of age. The definition of UTI is unclear and whether to proceed with micturating cystourethrography (MCUG) or 99mtechnetium-dimercaptosuccinic acid (DMSA) scintigraphy scan in this age group is controversial. Methods We retrospectively analyzed 29 neonates and infants younger than 2 months of age who underwent late DMSA scans 9 months following the first episode of febrile or symptomatic UTI between July 2009 and June 2016. Results In total, 192 children aged 0-24 months underwent ultrasound and DMSA scans (MCUG in 174/192). Neonates and infants younger than 2 months of age were significantly less likely to develop fever, and had a lower fever peak, shorter duration of fever before admission and after starting antibiotics, longer hospitalization period, lower C-reactive protein, and greater incidence of non-Escherichia coli infection. There was no difference in pyuria response at diagnosis. The prevalence rates of an ultrasound abnormality (28%), vesicoureteral reflux (28%), UTI recurrence (38%), and renal scarring (10%) in infants younger than 8 weeks of age were similar to those in children 2-24 months old. Conclusion Neonates and infants younger than 2 months of age with UTI warrant special consideration because the fever response used for diagnosis in older children may be absent or blunted. Clinical guideline is needed for the diagnosis and management of UTI in this age group.